Pengaruh Teknologi Artificial Intelligence (AI) terhadap Pembelajaran Bahasa Arab Siswa pada Jenjang Madrasah Aliyah - Kunti Nadiyah Salma (Lingua Franca, 2024)
This study aims to analyze the effect of Artificial Intelligence technology on Arabic language learning outcomes among tenth-grade Madrasah Aliyah students. This research employed a quantitative, quasi-experimental design with a pretest–posttest control-group model. The research data consisted of students’ learning outcome scores from tests administered before and after the treatment, while the data sources were the students themselves as research respondents. The study population consisted of all tenth-grade students at MAN Pacitan, and the sampling technique used was purposive sampling. The sample consisted of two classes: an experimental class that received AI-based learning and a control class that received conventional instruction. Data collection techniques included learning outcome tests, observation, and documentation. Data analysis was conducted using inferential statistics, beginning with prerequisite tests of normality and homogeneity, followed by an independent-samples t-test to determine differences in learning outcomes between the two groups. The results indicated a significant difference between students taught using Artificial Intelligence technology and those taught using conventional methods. Therefore, it can be concluded that the use of Artificial Intelligence technology has a positive, significant effect on students’ Arabic learning outcomes.